Enablers and barriers to the implementation of inclusive enterprise and supplier development in South Africa - Raziya, Ntombezintle (Graduate School of Business (GSB), 2023)
Despite the South African government's efforts to achieve inclusive growth, inequality persists. Enterprise and Supplier Development (ESD) was introduced to promote economic transformation for small, medium, and micro-enterprises (SMMEs). The conceptual framing of ESD is consistent with Social Innovation and Inclusive Innovation frameworks which advocate for inclusive innovation that disrupts social practices and relationships. There is a dearth of research on the implementation of ESD. This study asked: What are the enablers of, and the barriers to the implementation of inclusive ESD initiatives in South Africa? This qualitative study involved interviews with seven transformation managers, and five BBBEE consultants respectively. Key enablers to ESD implementation included visionary leadership, a visible shift in mindsets amongst some corporates', and an enabling legislative and policy environment. Barriers to ESD implementation included the legislative burden associated with B-BBEE, and lack of capacity amongst ESD actors. Evidence of ESD as an inclusive innovation initiative emerges through the strategic inclusion of beneficiary entities into corporate supply chains, and the pursuit of co-creative and symbiotic relationships. The study highlights the need for further research on leadership styles and monitoring and evaluation as enablers to the successful implementation of ESD. Practical recommendations include framing B-BBEE as a private equity fund and developing supply chains more strategically in an inclusive approach.